2014
DOI: 10.1080/01635581.2014.939291
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol: Inhibitory Effects on Metastatic Cell Behaviors and Voltage-Gated Na+Channel Activity in Rat Prostate Cancer In Vitro

Abstract: Resveratrol, a natural plant phenolic found at high concentration in red grapes, has been suggested to have a range of health benefits. Here, we tested its effects on metastatic cell behaviors. The strongly metastatic rat prostate MAT-LyLu cells were used as a model. At 20 μM, resveratrol had no effect on cellular proliferation or viability. However, it suppressed significantly 1) lateral motility by up to 25%; 2) transverse motility by 31%; and invasion by 37%. It also increased the cells' adhesion to substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…As a type of free radical scavenger and antioxidant, resveratrol is recognized as an effective anticancer compound in several types of cancer, such as leukemia (28), breast (2932), prostate (33) and ovarian cancers (34), melanoma (35) and primary brain tumors (36). In the present study, it was found that resveratrol may suppress renal carcinoma cell growth in a time- and dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…As a type of free radical scavenger and antioxidant, resveratrol is recognized as an effective anticancer compound in several types of cancer, such as leukemia (28), breast (2932), prostate (33) and ovarian cancers (34), melanoma (35) and primary brain tumors (36). In the present study, it was found that resveratrol may suppress renal carcinoma cell growth in a time- and dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Unbiased drug screens for inhibitors of cancer stem cells have implicated potassium ionophores such as salinomycin [358], and tetraethylammonium (TEA, a potassium channel blocker), was found to suppress colony formation in endometrial cancer cells while withdrawal of TEA resulted in a significant enhancement of tumorigenesis [359]. Known cancer-fighting agents are now beginning to be recognized as ion channel modulators, for example resveratrol [360][361][362]. Indeed, drugs that target membrane voltage-generating transporters have already shown clinical promise in cancer [363].…”
Section: Ion Channels Are Oncogenes and Important Drug Targetsmentioning
confidence: 99%
“…[20] In addition, resveratrol has shown to attenuate several voltage gated ion channels in several cell lines. Mainly resveratrol inhibited voltage gated sodium current in rat prostate cancer cell line (MAT-LyLu) [11] and Kv1.3 in human lymphocytes. [21] Our obtained result shows that perfusion of 200 µM of resveratrol inhibited I K current in LNCaP cells.…”
Section: Discussionmentioning
confidence: 99%
“…Especially curcumin and resveratrol exerts a modulatory effect on several ion channels, including voltage gated sodium and potassium channels. [11][12][13] However, to date, no studies investigated the modulatory effect of phenolic compounds curcumin, resveratrol, rutin, and troxerutin on voltage gated K + channel in human prostate cancer cell line LNCaP.…”
Section: Introductionmentioning
confidence: 99%